2008
DOI: 10.1088/0960-1317/19/1/015021
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of parametric and externally forced motion in resonant MEMS sensors

Abstract: In this paper an excitation method employing both harmonic forcing and parametric excitation is applied to a resonant MEMS sensor in order to investigate and characterize the phenomena of parametric resonance and parametric amplification. The motivation for this research is that parametric excitation may be used to significantly reduce the total damping in MEMS sensors in a controllable manner. This is extremely pertinent to devices where the Q-factor is a principal factor in determining sensor performance. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 30 publications
(64 reference statements)
0
43
0
Order By: Relevance
“…From the tests conducted in [3] it was shown that the threshold voltage for parametric resonance was experimentally determined to be of the order V . Experimental tests were performed with a series of different forcing levels to determine the validity of the linear model and to determine the minimum level of forcing that may be used practically with this experimental setup.…”
Section: Experimental Results For the Parametrically Amplified Resonamentioning
confidence: 99%
See 3 more Smart Citations
“…From the tests conducted in [3] it was shown that the threshold voltage for parametric resonance was experimentally determined to be of the order V . Experimental tests were performed with a series of different forcing levels to determine the validity of the linear model and to determine the minimum level of forcing that may be used practically with this experimental setup.…”
Section: Experimental Results For the Parametrically Amplified Resonamentioning
confidence: 99%
“…the forcing voltage f V must be considerably reduced from the value of 100 mV used in the low gain experiments reported in [3]. Attenuation of the harmonic forcing signal was performed via a resistor network after the signal generation to avoid distortion and to provide impedance matching between signal generator, digitizer and the MEMs device.…”
Section: Experimental Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations
“…With the rapid development of technology, functionally graded (FG) beams and plates are often used in MEMS/NEMS, such as the components in the shape of memory thin films alloy with a global thickness in the micro/nano scale, atomic force microscopes (AFMs), and electrically actuated MEMS devices [1][2][3][4][5][6][7][8]. As opposed to the strain theories which were introduced by Mindlin and Eshel [9], with five constants besides the Lamé constants, Lam et al [1] presented a modified theory consisting of only three non-classical constants.…”
Section: Introductionmentioning
confidence: 99%